Growth, Inequality and Social Institutions - Andrea Brandolini; Nicola Rossi (Luxembourg Income Study (LIS), 1995)
This paper examines the relationship between inequality and economic growth in 18 LIS countries. They begin with a discussion of the fact that issues of conceptual and statistical comparability are essential to the understanding and measurement of the growth-equality relationship and their neglect actually undermines most of the available empirical evidence. The authors' findings suggest that recent emphasis on the role of political institutions in this link might be misplaced and instead favor exploring the cross-country differences in social institutions. They predict that productivity growth might be stimulated by the presence of equality enhancing social institutions.
Keywords: 330; Einkommensverteilung; Haushaltseinkommen; Wirtschaftswachstum; Industrieländer